Comparative Study of Encryption Algorithms for Data Security in WoT and IoT - et. al., Baraa Mohammed Hassan , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, both the Web of Things (WoT) and the Internet of Things (IoT) have become important areas in every aspect of our lives. This technology is supposed to link billions of devices, which leads to an enormous number of communications between devices that will produce a huge amount of sensitive information, and to protect that information from unauthorized persons to access and manipulate it. Given this, encryption algorithms are introduced as a solution to protect the security of sensitive information. In this paper, algorithms of encryption are compared for the security of data.